Complete genome sequence of Polynucleobacter necessariussubsp. asymbioticus type strain (QLW-P1DMWA-1T). Issue 1 (January 2012) - Meincke, Linda; Copeland, Alex; Lapidus, Alla; Lucas, Susan; Berry, Kerrie; Glavina Del Rio, Tijana; Hammon, Nancy; Dalin, Eileen; Tice, Hope; Pitluck, Sam; Richardson, Paul; Bruce, David; et al.
Abstract Polynucleobacter necessarius subsp.asymbioticus strain QLW-P1DMWA-1T is a planktonic freshwater bacterium affiliated with the familyBurkholderiaceae (classBetaproteobacteria ). This strain is of interest because it represents a subspecies with cosmopolitan and ubiquitous distribution in standing freshwater systems. The 16S-23S ITS genotype represented by the sequenced strain comprised on average more than 10% of bacterioplankton in its home habitat. While all strains of the subspeciesP. necessarius asymbioticus are free-living freshwater bacteria, strains belonging to the only other subspecies, P. necessarius subsp.necessarius are obligate endosymbionts of the ciliateEuplotes aediculatus . The two subspecies ofP. necessarius are the instances of two closely related subspecies that differ in their lifestyle (free-livingvs. obligate endosymbiont), and they are the only members of the genusPolynucleobacter with completely sequenced genomes. Here we describe the features ofP. necessarius subsp.asymbioticus, together with the complete genome sequence and annotation. The 2, 159, 490 bp long chromosome with a total of 2, 088 protein-coding and 48 RNA genes is the first completed genome sequence of the genusPolynucleobacter to be published and was sequenced as part of the DOE Joint Genome Institute Community Sequencing Program 2006.